PROPERTIES OF ISOQUINALIN AND ITS HOMOLOGUES, IMPORTANCE IN HUMAN LIFE (Web of Teachers: Inderscience Research, 2024)
Isoquinaline and its homologues are compounds that play an important biological role in the human body. A deeper understanding of their properties and importance in human life will help to understand their place in scientific research and practice. This article provides detailed information on the composition, properties, biological activity and effects on human health of isoquinaline and its homologues.